Dakwah Sebagai Resolusi Sosial Terhadap Penyimpangan Sosial Di Masyarakat Lombok - Heriyadi (STAI Bumi Silampari, 2025)
This study aims to analyze the role of da'wah as a social resolution to various forms of social deviance occurring in Lombok society. Social phenomena such as moral decline, promiscuity, drug abuse, and the weakening of mutual cooperation values indicate serious challenges in the social life of a society facing the currents of modernization and globalization. In this context, da'wah functions not only as a means of conveying religious teachings, but also as a social mechanism capable of guiding, controlling, and correcting community behavior so that it remains in line with moral and religious values. This research uses a qualitative approach by examining the religious social phenomena of the Sasak community in Lombok. The results of the study show that dakwah plays a significant role in shaping social awareness and strengthening community solidarity through the teachings of amar ma'ruf nahi munkar. Dakwah in Lombok is carried out through various approaches, including dakwah bi al-lisan (lectures and recitations), dakwah bi al-hal (social actions such as economic empowerment, cleanliness, and the environment), and dakwah based on local culture such as Maulid Adat and zikir together. In addition, the role of religious leaders such as Tuan Guru and Islamic boarding schools (pesantren) are key pillars in instilling Islamic values and maintaining community morality. The cultural approach, use of local languages, and synergy between religious scholars, traditional leaders, and village governments have made da'wah in Lombok effective in preventing and addressing social deviance. Thus, da'wah in Lombok not only functions as a spiritual activity, but also as a social resolution that can strengthen religious values, foster solidarity, and maintain social balance amid the dynamics of changing times.